General Self-efficacy and Other Predictors of Grade Point Average (GPA) in College Students of Kathmandu, Nepal - Poudel, Dev Bandhu; Acharya, Samjhana (International Research Journal of MMC, 2024)
General self-efficacy refers to individuals’ belief in their ability to manage their functioning and influence life events. It can be influenced by various factors such as personal achievements, observed experiences, encouragement, and emotional states. We aimed this study to examine the relationship between general self-efficacy and other demographic factors in predicting Grade Point Average (GPA) among college students. The power analysis indicated minimum of 385 data points for unknown population, however we followed the rules of thumb that more data equals better results. This cross-sectional survey involved 527 college students from the Kathmandu Valley, representing various age groups, genders, ethnicities, religious affiliations, marital statuses, residential locations, education levels, faculties, and years of study. We targeted only two colleges to collect the data; however, the online portal of data collection allowed students to provide the data from other institutions as well. Students were selected through opportunity sampling, and data were collected using the General Self-Efficacy Scale between September 8 and November 2, 2022. Our findings indicate no significant relationship between general self-efficacy and GPA. Ethnicity (Janajati), religion (Buddhists), education level (high school), faculty (management), and institution type (private) were identified as significant predictors of GPA, while gender, age, marital status, and residential location did not predict GPA. The study provides valuable insights into how demographic factors, rather than self-efficacy, influence academic performance, offering useful information for educational strategies aimed at improving student outcomes.